Tata Kelola Pasar dan Strategi Pemasaran Kajian Arthasastra (Jurnal Manajemen dan Ekonomi (JME), 2026)
This article examines the concept of market governance and marketing strategy in the Arthasastra and its relevance to modern marketing practices and market regulation. Contemporary marketing theories that emphasize efficiency and profit maximization often marginalize ethical considerations, justice, and consumer protection. As an alternative framework, the Arthasastra presents an economic paradigm that views the market as a social institution subject to state regulation in order to maintain economic stability and public welfare. This study employs a qualitative library research approach through textual analysis of the Arthasastra and relevant literature on Hindu economics, business ethics, and modern marketing theory. The findings indicate that market governance in the Arthasastra is grounded in price regulation, quality standards, trade supervision, and consumer protection. Marketing strategy is implicitly articulated through normative principles emphasizing honesty, fair pricing, product quality, and long-term trust-building. Dharma serves as an ethical foundation that integrates economic objectives with social justice. These findings highlight the theoretical relevance of the Arthasastra as an alternative conceptual source for developing ethical, just, and sustainable marketing models.
Keywords: Arthasastra, market governance, marketing strategy, consumer protection, business ethics